Analisa ANALISA FAKTOR-FAKTOR PENYEBAB CHANGE ORDER PADA PROYEK PENINGKATAN JALAN INSPEKSI JALAN DUYUNG (LANJUTAN) - Novia Siti Rohana (Racic : Rab Construction Research, 2018)
ABSTRACT Change Order (CO) is a change of work in a construction project. CO is very difficult to avoid and if this change order occurs it can harm the project. In view of its relevance, the project for upgrading the road for the duyung road inspection (continued) has a high risk of change orders. This must be minimized from the beginning of the project work, one of which is by identifying the fundamental factors that cause change order on this project, using descriptive analysis methods. Based on literature review and interviews, this study identified 11 factors causing change order. Data that has been collected through questionnaires with a total of 50 respondents involved in this study. These respondents were all people who worked on the project. Each respondent was asked to express his opinion about frequency and the impact caused using a Likert scale 1-5. Two factors are classified as the most important factors causing change contract orders from the most dominant ones, namely physical conditions in the field (1) and changes in scope of work (2) and non-dominant factors, namely the problem of the supervisor consultant (1) and the problem of the contractor (2). This descriptive analysis also shows a positive and statistically significant correlation. Keywords: Change Order, Project, Construction, Water Building, Descriptive Analysis